Capitalism, Class and Revolution in Peru, 1980-2016 - Lust, Jan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In an analysis of political, economic, and social development in Peru in the years between 1980 and 2016, this book explores the failure of the socialist Left to realize its project of revolutionary social transformation. Based on extensive interviews with leading cadres in the struggle for revolutionary change and a profound review of documents from the principal socialist organizations of the 1980s and 1990s, the volume reveals that the socialist Left did not fully comprehend the deep political and social implications of changes to the country's class structures. As such, the Left failed to develop and implement adequate strategic and tactical responses to the processes that eroded its political and social bases in the 1980s and 1990s, ultimately leading to its loss of social and political power. Lust concludes that the continued political and organizational agony of the Peruvian socialist Left and the hegemony of neoliberalism in society is a product of the dialectical interplay between the objective and subjective conditions that determine Peruvian capitalist development.
Introduction -- 1. Neoliberalism and the Socialist Left in Peru: An Epochal Change -- 2. Class and Class Structure in Peru -- 3. Capitalist Economic Development in Peru: 1980-2016 -- 4. The Changing Class Structure of Peru: 1980-2014 -- 5. The Class Struggle and the Left: 1980-2016 -- 6. The Erosion of the Political and Social Bases of the Socialist Left -- Conclusion.
Keywords: Political sociology; Social structure; Equality; Economic sociology; America -- Politics and government; Latin America -- Economic conditions; International economic relations; Political Sociology; Social Structure; Economic Sociology; American Politics; Latin American/Caribbean Economics; International Political Economy'.